2018
DOI: 10.4317/medoral.21319
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith-Wiedemann Syndrome: Open bite evolution after tongue reduction

Abstract: BackgroundMacroglossia causes functional deficits such as airway obstruction, drooling, phonation difficulties, and leads to protrusion of dentoalveolar structures resulting in an anterior open bite and a prognathic mandibular appearance. Macroglossia is present in the majority of patients with Beckwith-Wiedemann syndrome (BWS) and surgical treatment may be indicated.Material and MethodsA retrospective review was conducted including BWS patients who underwent surgical tongue reduction between 2000 and 2015 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 23 publications
0
43
0
5
Order By: Relevance
“…This leads us to hypothesize that the incidence of skeletal class III in patients with BWS is substantially lower than hitherto reported. Most of the data provided in the literature rely on single case reports or small case series involving a limited number of children [ 16 , 17 , 32 , 37 ]. Although macroglossia might stimulate mandibular growth, it is difficult to determine whether the prognathism of the mandibular basis is a result of macroglossia and dentoalveolar changes or if it is genetically driven [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads us to hypothesize that the incidence of skeletal class III in patients with BWS is substantially lower than hitherto reported. Most of the data provided in the literature rely on single case reports or small case series involving a limited number of children [ 16 , 17 , 32 , 37 ]. Although macroglossia might stimulate mandibular growth, it is difficult to determine whether the prognathism of the mandibular basis is a result of macroglossia and dentoalveolar changes or if it is genetically driven [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indications for tongue reduction surgery (TRS) have not been clearly defined. While some studies recommend early surgical treatment of macroglossia to prevent mandibular prognathism and open bite, others demonstrated that TRS does not control the pattern of mandibular growth and the development of class III skeletal malocclusion [ 16 , 17 , 18 , 19 ]. Indeed, the enlarged mandibular body observed in BWS might be caused by mandibular cartilaginous growth activated by IGF-2 expression, rather than being secondary to tongue overgrowth [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For most people with macroglossia, an oversized tongue can completely block the airways, leading to suffocation and sudden death ( Alonso-Rodriguez et al, 2018 ). Patients with macroglossia need closely monitored and lifesaving measures such as tracheotomy ( Junghaenel et al, 2012 ).…”
Section: Macroglossia Diseasementioning
confidence: 99%
“…Macroglossia in BWS becomes less noticeable with age and often requires no treatment; but it does cause problems for some children with BWS. In severe cases, macroglossia can cause respiratory, feeding, and speech difficulties may require surgery [20]. It is seen in about 90% of patients with BWS [7].…”
Section: ) Hepatoblastomamentioning
confidence: 99%